Organisational justice and psychological well-being of employees in the local government service of Osun state, Nigeria (2015)
"An individual's perception of and reactions to fairness in an organisation, is fundamental to human psychological and social interaction. The feeling of justice, be it promotional decision, assignment of tasks, allocation of rewards are germane to the psychological well-being of employees. It is against this background that the research looks into organisational justice and psychological well-being of employeesin the local government service of Osun State, Nigeria. The descriptive research design of the expost facto was used for the research. The population of this study consisted of staff of the Ministry of Local Government and all employees of the thirty Local Government Councils in Osun State. A multi-stage sampling technique was used for the selection of the 317 respondents used for the research. The main instrument used for the study is a questionnaire tagged ""Organisational Justice and Employees' Psychological Wellbeing Questionnaire (OJAEPWQ)"" with four sub-sections namely Distributive Justice Scale (DJS), Procedural Justice Scale (PJS), Interactional Justice Scale (IJS), Psychological Wellbeing Scale (PWS) with reliability coefficient of 0.79, 0.90, 0.86 and 0.87 respectively. Two research questions and three hypotheses were analyzed using multiple regression analysis and Pearson Product Moment Correlation at 0.05 level of significance. Findings showed the joint contribution of the three independent variables to the prediction of the dependent variable is significant (F(3,313)= 181.203). The relative contribution of the three independent variables to the dependent variable, expressed as beta weights are Distributive justice (β = 150, t=3.436, P<.05), Procedural justice (β= .247, t=5.537, P <.05) and Interactional justice (β= .511, t=10.305, P<.05). Furthermore, it was revealed that there was a significant relationship between distributive justice and psychological well-being (r=.583, n=317, P <.05). There was a significant relationship between procedural justice and psychological well-being (r=.643, n=317, P < .05) and that there was a significant relationship between interactional justice and psychological well-being (r = .760, n = 317, P < .05). Based on the above findings it was recommended that managements in organisations should give room for justice in such a way that the psychological well-being of employees in terms of their thoughts, feelings, emotions, understanding, perception and interpersonal relations are protected among others. "